Correction of therapy of concerned cardiovascular disease and chronic obstructive pulmonary disease in a patient with pulmonary tuberculosis - Natalia V. Bagisheva; Anna V. Mordyk; Dmitry I. Trukhan; Inna A. Viktorova; Marina V. Moiseeva; Anna R. Aroyan; Svetlana V. Sitnikova (LLC "MEDIAFORMAT", 2021)
Chronic obstructive pulmonary disease and cardiovascular diseases (arterial hypertension, coronary heart disease, chronic heart failure) are among the comorbid conditions that mutually aggravate each other. The addition of tuberculosis in this category of patients requires additional efforts from the doctor to improve treatment outcomes. A clinical example of correction of therapy for arterial hypertension and chronic obstructive pulmonary disease in a patient with pulmonary tuberculosis is presented.